SCIENTIFIC AND PRACTICAL APPROACHES TO THE DETERMINATION OF SPATIAL PROVISION OF ENVIRONMENTAL MONITORING OF LAND USE IN THE URBAN ENVIRONMENT - Frolov, V. (Municipal economy of cities. Series: «Economy science», 2023)
The current state of spatial provision of ecological monitoring of land use in the urban environment is characterized by ambiguous theoretical and practical approaches, which are determined by regulatory rules and quantitative indicators. There are several problems that affect the spatial provision of ecological monitoring of land use in the urban environment. Stakeholder relations for the formation of strategic contours of environmental policy: are formed and implemented by: - implementation of education in the interests of balanced (sustainable) development, environmental education and upbringing, educational activities with the aim of forming environmental values in society and increasing its environmental awareness; - assessment of the attitude and raising the level of public awareness regarding the importance, benefits and tools of sustainable consumption and production, the state and values of biodiversity and the measures that must be taken for its preservation, restoration and sustainable use; - ensuring the practical implementation of the results of modern and fundamental ecological research and continuous interaction between scientists and state bodies; taking into account the recommendations of environmental scientific institutions when making management decisions and preparing drafts of normative legal acts; - development of partnership between sectors of society in order to involve all interested parties in the planning and implementation of environmental policy; ensuring public participation in management decision-making in the field of environmental protection and nature management; - ensuring compliance with the environmental rights and responsibilities of citizens, public access to justice in matters of environmental protection and nature use. The purpose of the article is to research modern approaches to determining the spatial provision of ecological monitoring of land use in the urban environment. As a result of the research, the proposed author’s definition of spatial provision of ecological monitoring of land use in the urban environment as a system of formation and use of information provision and control over the use of information on the ecological state of land use in the urban environment with the use of modern technological means and geo-information systems, taking into account the peculiarities and directions of interaction with various by groups of interested persons (stakeholders), including state and local institutions, aimed at increasing the efficiency of land use and environmental safety. Special attention is paid to the study of the impact of ecological components on individual land plots, the peculiarities of their registration, the creation of land management documentation and the accumulation of cadastral information during the implementation of monitoring processes. Research has a significant place in the development of urban land use monitoring and the sustainable development of cities in general.